2020
DOI: 10.1186/s13287-020-01611-z
|View full text |Cite
|
Sign up to set email alerts
|

Priming with inflammatory cytokines is not a prerequisite to increase immune-suppressive effects and responsiveness of equine amniotic mesenchymal stromal cells

Abstract: Background: Equine amniotic mesenchymal stromal cells (AMSCs) and their conditioned medium (CM) were evaluated for their ability to inhibit in vitro proliferation of peripheral blood mononuclear cells (PBMCs) with and without priming. Additionally, AMSC immunogenicity was assessed by expression of MHCI and MHCII and their ability to counteract the in vitro inflammatory process. Methods: Horse PBMC proliferation was induced with phytohemagglutinin. AMSC priming was performed with 10 ng/ml of TNF-α, 100 ng/ml of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Our functional studies using in vitro stimulated lymphocytes (that partially mimic an antigen-specific activation of T cells) could demonstrate their immunomodulatory capacity, however, further studies need to be performed to identify targeted genes in different immune cells. In a very recent study (81) equine amniotic MSCs were primed with a combination of IFNγ and TNFα demonstrating no additional immunosuppressive activity in an inflammatory in vitro model, compared to non-primed cells. Even though this study was performed with lower concentrations of IFNγ and TNFα on a different type of MSCs, it remarks that further research is necessary to confirm our insights.…”
Section: Discussionmentioning
confidence: 99%
“…Our functional studies using in vitro stimulated lymphocytes (that partially mimic an antigen-specific activation of T cells) could demonstrate their immunomodulatory capacity, however, further studies need to be performed to identify targeted genes in different immune cells. In a very recent study (81) equine amniotic MSCs were primed with a combination of IFNγ and TNFα demonstrating no additional immunosuppressive activity in an inflammatory in vitro model, compared to non-primed cells. Even though this study was performed with lower concentrations of IFNγ and TNFα on a different type of MSCs, it remarks that further research is necessary to confirm our insights.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment is usually associated with immunosuppressive cells, which have negative effects on the activation, migration, and proliferation of T cells. MDSCs, immature DCs, macrophages, and Tregs [ 65 ] are known to have key roles in the tumor microenvironment [ 66 ]. Many Treg-specific epigenetic characteristic genes, such as CTLA4 , IKZF4 (EOS), and TNFRSF18 (GITR), show complete demethylation, which allows fork box P3 (FOXP3) T cells to obtain Treg characteristic gene expression, lineage stability, and specific immunosuppressive activity [ 67 ].…”
Section: Gene Expression Changes Caused By Epigenetic Modificationmentioning
confidence: 99%
“…It has also been suggested that several types of PnD can be used for allogeneic transplantation without rejection because they show hypo immunogenicity and the ability to modulate immune responses ( Li et al, 2017 ; Ling et al, 2019 ). Compared to bone marrow-MSC, that are not able to exert suppressive effects if they are not previously exposed to inflammatory stimuli, PnD do not require “licensing” with inflammatory stimuli such as interferon (IFN) and tumor necrosis factor-α (TNF-α) ( Lange-Consiglio et al, 2020 ; Papait et al, 2020 ). Moreover, PnD produce higher levels of cytokines and growth factors as compared to bone marrow-MSC and adipose-MSC, including granulocyte colony-stimulating factor (G-CSF), regulated on activation, normal T cell expressed and secreted (RANTES) and interleukin (IL)-6/-8/-10 ( Seok et al, 2020 ).…”
Section: Perinatal Derivatives (Pnd)mentioning
confidence: 99%